Anonymous art at auction : the reception of early Flemish paintings in the Western art market (1946-2015) - Radermecker, Anne-Sophie (Studies in the history of collecting & art markets ;, 2021)
"Working with a data set accounting for 13,000 auction sales results, Anne-Sophie V. Radermecker explores what contemporary buyers value when purchasing paintings of unknown or uncertain authorship, and which variables influence price formation mechanisms in this market segment. The principle finding of this book is not only that historical names matter in the art market, but so do all other alternative identification strategies that art market players use to label anonymous paintings. Indirect names, provisional names, and spatiotemporal designations function as substitutes for real names that simulate identities, create ex-post stories around the artworks offered for sale, and, consequently, reduce information asymmetry about an artist's identity, with, at time, quite unexpected effects on price"--